Performance and Emission Characteristics of Spark Ignition Engine Fuelled with Ethanol and Methanol Gasoline Blended Fuels - Gravalos, Ioannis; Moshou, Dimitrios; Gialamas, Theodoros; Xyradakis, Panagiotis; Kateris, Dimitrios; Tsiropoulos, Zisis (IntechOpen, 2011)
None